IMPLEMENTASI KURIKULUM MUATAN LOKAL BERBASIS KEARIFAN LOKAL DI KABUPATEN ACEH BARAT - Masni Masni; Syahwaluddin; Musayyada; Wirda Wahyuni; Shella Wati (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
This study aims to examine the implementation of a local content curriculum based on local wisdom in West Aceh Regency. The local content curriculum plays an important role in the education system because it serves to introduce and preserve the cultural, social, and spiritual values that have developed in the local community and are in line with the principles of Islamic law. This study uses a quantitative approach with data collection techniques in the form of distributing questionnaires to respondents from various levels of education. The collected data was then analyzed using descriptive statistical methods. The results of the study show that the implementation of a local content curriculum based on local wisdom in West Aceh Regency has been carried out well, with an achievement rate of 87% of the ideal score. Teachers also showed high enthusiasm for the implementation of this curriculum because it was considered capable of helping to preserve regional culture while increasing students' knowledge and understanding of Aceh's local wisdom